Do Ventilator Bundles Reduce Ventilator-Associated Pneumonia? A Meta-Analysis of Randomized Controlled Trials - Reski Anugrah Zuandra; Irvan Medison; Russilawati (HM Publisher, 2025)
Background: Ventilator-associated pneumonia (VAP) is a serious complication in mechanically ventilated patients, leading to increased morbidity, mortality, and healthcare costs. Ventilator bundles are evidence-based practices aimed at preventing VAP. This meta-analysis evaluated the effectiveness of ventilator bundles in reducing VAP incidence in critically ill adults. Methods: A systematic search of PubMed, Embase, and Cochrane Central Register of Controlled Trials was conducted from January 2013 to December 2024. Randomized controlled trials (RCTs) comparing ventilator bundles to standard care in adult patients receiving mechanical ventilation were included. The primary outcome was the incidence of VAP. Secondary outcomes included mortality, length of intensive care unit (ICU) stay, and duration of mechanical ventilation. Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using a random-effects model. Results: Nine RCTs involving 2,850 patients met the inclusion criteria. The implementation of ventilator bundles was associated with a significant reduction in VAP incidence (RR 0.68, 95% CI 0.55-0.84, p=0.0002). Mortality (RR 0.89, 95% CI 0.75-1.05, p=0.16) and duration of mechanical ventilation (mean difference -1.2 days, 95% CI -2.8 to 0.4, p=0.13) did not significantly differ between groups. However, a significant reduction in ICU length of stay was observed in the ventilator bundle group (mean difference -2.1 days, 95% CI -3.5 to -0.7, p=0.004). Conclusion: This meta-analysis demonstrates that ventilator bundles are effective in reducing VAP incidence in critically ill adults. While no significant impact on mortality was observed, ventilator bundles were associated with a shorter ICU length of stay. These findings reinforce the importance of implementing ventilator bundles as a standard of care in ICUs to improve patient outcomes.